Molecular and clinical features of papillary thyroid cancer in adult patients with a non-classical phenotype - Zhou, Jie; Wang, Wei-Ran; Zhang, Hui-Fang; Gao, Qi-Qi; Wang, Wei-Bin; Zhu, Jian-Hua; Han, Yu-Shuai; Chen, Jing; Ma, Tong-Hui; Zhang, Xiao-Yan; Teng, Xiao-Dong (Frontiers in Endocrinology, 2023)
Purpose: Genotyping is fundamental in papillary thyroid cancer (PTC) and helps to enhance diagnosis and prognosis and determine appropriate treatments. The phenotype-genotype association in PTC was previously studied, with BRAF V600E characterizing classic PTC and tall-cell PTC and RAS mutations characterizing follicular-variant PTC. In clinic, some non-classical histological subtypes of PTC were also identified, however, their genotype remains unclear. In this study, we collected samples of these non-classical PTC after the exclusion of classic phenotypes and examined their phenotypes, genotype and the relationship between phenotype and genotype. Methods: We screened out non-classical PTC by excluding classical PTC from 1,059 different thyroid samples, and a total of 24 cases was obtained and described from the morphological features, which is rare in differentiated PTC. DNA/RNA sequencing was performed using 18 available samples to describe the genetic features. Results: PTC with the non-classical phenotype were characterized cuboidal to low columnar tumor cells with subtle nuclear features of PTC and without discernible nuclear elongation, concurrently with dense microfollicles, delicate papillae or solid nodules with delicate fibrovascular cores. They were associated with lymphatic vessel invasion (P<0.001) but not with a worse prognosis (P=0.791). Gene fusions were identified in 14 of 18 (77.8%) cases, including eight fusions of NTRK and six fusions of RET. The high percentage of fusions in this papillary thyroid cancer subgroup suggested a correlation of gene fusions with the phenotype that does not belong to the BRAF V600E-mutant or RAS-mutant group. Conclusions: Our study retrospectively screened a large cohort of different thyroid tissue samples, and presented the histopathological and genetic features of a non-classical phenotype of PTC from 24 patients. It may contribute to diagnose in PTC, and patients of these non-classical phenotype may benefit from targeted therapy, compared to a natural patient cohort without selection.